1986
DOI: 10.1128/iai.52.1.18-25.1986
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of mouse small intestine mucosal receptors for Escherichia coli K-12(K88ab)

Abstract: Adhesion of 3H-labeled Escherichia coli K-12(K88ab) to CID-I mouse small intestine mucus and brush border preparations, immobilized on polystyrene, was studied. E. coli K12(K88ab) was shown to adhere readily to either crude mucus or brush border preparations, but not to bovine serum albumin. In contrast, the nearly isogenic E. coli K-12 strain, i.e., lacking the K88ab plasmid, did not bind well to either mucus, brush borders, or bovine serum albumin. The adhesion of E. coli K-12(K88ab) to both mucus and brush … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 38 publications
(43 reference statements)
0
56
0
Order By: Relevance
“…to adhere to immobilised crude mucus has been previously described in di¡erent species of animals [17,25]. The K88 adhesin exists in at least three antigenic forms, i.e., K88ab, K88ac, and K88ad, which appear to have adhesive speci¢city for brush border membranes isolated from pigs of di¡erent phenotype [2,3,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…to adhere to immobilised crude mucus has been previously described in di¡erent species of animals [17,25]. The K88 adhesin exists in at least three antigenic forms, i.e., K88ab, K88ac, and K88ad, which appear to have adhesive speci¢city for brush border membranes isolated from pigs of di¡erent phenotype [2,3,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, Sellwood et al [19] and Anderson et al [22] reported that glycoproteins are involved in the attachment of K88 ¢mbriae to intestinal epithelial cells. Laux et al [12] have also shown that the receptors to K88 ¢mbriae present in mouse small intestinal mucus are glycoproteins, which may contain D-galactosamine or D-galactosamine-like residues.…”
Section: Discussionmentioning
confidence: 97%
“…The adhesion of radioactively labeled E. coli cells to the intestinal mucus of 14-day-old piglets was studied by using a modi¢cation of the methods of Laux et al [12]. All adhesion assays were performed in triplicate in multiwell polystyrene tissue culture plates (Linbro, £at bottom, 1.6 cm : Nunc, polysorp).…”
Section: In Vitro Adhesion Assaymentioning
confidence: 99%
See 2 more Smart Citations